Dampak Pandemi dan Ekonomi Makro Terhadap Return Saham(Studi Kasus Pada Perusahaan Food And Beverage Yang Terdaftar Di BEI Periode 2016-2020) - Saefudin; Sulaiman Kurdi; Muhammad Fauzi (Jurnal Ekonomika dan Bisnis, 2022)
The impact of the pandemic has ravaged the world economy, which in the end has resulted in the performance of many companies including food and beverage sector companies that are listed on the Indonesia Stock Exchange (IDX). This study aims to analyze the impact of the pandemic and macroeconomics on stock returns of food and beverage sector companies listed on the IDX for 2016-2020 period. The sample in this study used a purposive sampling method with the number of companies that matched the criteria as many as 13 companies in the food and beverage sector. The data were tested statistically through a multiple linear regression analysis approach that already met the classical assumption criteria. The results showed that the pandemic (α: 1%), the exchange rate (α: 10%), interest rates (α: 5%), and inflation (α: 5%) were proven to significantly reduce stock returns. Empirically proves that the pandemic variable is the most influential factor in reducing stock returns compared to exchange rates, interest rates, and inflation.